The coulomb glory effect in collisions of antiprotons with heavy ions - Maiorova, Anaa V.; Stöhlker, Thomas (Russian journal of physical chemistry. B, Focus on physics, 2012)
The Coulomb glory effect in the back scattering of antiprotons with energies of from 100 eV to 3 keV from a bare nucleus of uranium and from uranium ions with closed shells is considered in terms of nonrelativistic and relativistic quantum theory. The appearance of Coulomb glory in collisions with multiply charged ions is caused by nucleus charge screening by filled electron shells. In scattering from a bare nucleus, the effect appears because of the screening properties of the vacuum polarization potential.